Private sector promotion of agricultural technologies: Experimental evidence from Nigeria - Liverpool-Tasie, Lenis Saweda O.; Dillon, Andrew; Bloem, Jeffrey R.; Adjognon, Guigonan Serge (Elsevier, 2025)
Private sector agricultural businesses are critical for scaling new and potentially environmentally-friendly technologies, though much attention has focused on public agricultural investment. Working with a private firm, we conduct an experiment testing the effectiveness of alternative marketing strategies for promoting the adoption of urea super granule fertilizer (USG) among rice farmers in Nigeria. We disentangle the effects of price discount vouchers and the firm’s standard marketing package. We find that the firm’s standard marketing increases the adoption of USG fertilizer by 24 percentage points while reducing prilled urea utilization by 17 percentage points. Discount vouchers increase adoption of USG by an additional eight percentage points, but are not profitable for the firm. Although the adoption of USG leads to substantial environmental benefits by reducing nitrogen loss, farmer rice yields did not increase. Thus, despite the potential public benefits, private incentives facing firms and farmers are insufficient to drive scaling after a one-year intervention.